The Importance of Telemedicine during COVID-19 Pandemic: A Focus on Diabetic Retinopathy - Raffaele Galiero; Pia Clara Pafundi; Riccardo Nevola; Luca Rinaldi; Carlo Acierno; Alfredo Caturano; Teresa Salvatore; Luigi Elio Adinolfi; Ciro Costagliola; Ferdinando Carlo Sasso (Journal of Diabetes Research)
Recently, telemedicine has become remarkably important, due to increased deployment and development of digital technologies. National and international guidelines should consider its inclusion in their updates. During the COVID-19 pandemic, mandatory social distancing and the lack of effective treatments has made telemedicine the safest interactive system between patients, both infected and uninfected, and clinicians. A few potential evidence-based scenarios for the application of telemedicine have been hypothesized. In particular, its use in diabetes and complication monitoring has been remarkably increasing, due to the high risk of poor prognosis. New evidence and technological improvements in telemedicine application in diabetic retinopathy (DR) have demonstrated efficacy and usefulness in screening. Moreover, despite an initial increase for devices and training costs, teleophthalmology demonstrated a good cost-to-efficacy ratio; however, no national screening program has yet focused on DR prevention and diagnosis. Lack of data during the COVID-19 pandemic strongly limits the possibility of tracing the real management of the disease, which is only conceivable from past evidence in normal conditions. The pandemic further stressed the importance of remote monitoring. However, the deployment of device and digital application used to increase screening of individuals and monitor progression of retinal disease needs to be easily accessible to general practitioners.